2009
DOI: 10.1177/0883073809336677
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Palsy—Long-Term Medical, Functional, Educational, and Psychosocial Outcomes

Abstract: Cerebral palsy, typically diagnosed in childhood, clearly continues into adulthood. This study describes the long-term medical, functional, educational, and psychosocial outcomes of people with cerebral palsy. Of the 203 people with cerebral palsy diagnosed and treated at the Child Development Center in Tel Aviv between 1975 and 1994, 163 (80%; age range 8-30 years, mean age 18.9 years, and median age 19 years) participated in a cross-sectional telephone survey. Half the respondents have chronic health problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 35 publications
4
30
0
Order By: Relevance
“…1-3 Cerebral palsy is characterized by non-progressive disorders of movement and posture, presumed to result from insult to the brain during fetal or early infant life. 4 These motor problems are often accompanied by disturbances of cognition and other neurologic difficulties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1-3 Cerebral palsy is characterized by non-progressive disorders of movement and posture, presumed to result from insult to the brain during fetal or early infant life. 4 These motor problems are often accompanied by disturbances of cognition and other neurologic difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…4 These motor problems are often accompanied by disturbances of cognition and other neurologic difficulties. 1, 3, 4 Cerebral palsy can be a severe handicap and a substantial burden for the family and society.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Cerebral palsy is characterized by non-progressive disorders of movement and posture, presumed to result from insult to the brain during fetal or early infant life. 4 These motor problems are often accompanied by disturbances of cognition and other neurologic difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of outpatient care generally, it is unclear whether youth or adults with CP receive more care. Some studies found that adults with CP used outpatient services (e.g., visits to physicians in emergency rooms and specialists) more frequently than youth (Goodman et al, 2011;Young et al, 2007), while other studies reported the opposite pattern (Mesterman et al, 2010;Stevenson, Pharoah, & Stevenson, 1997). In terms of satisfaction with health care services, results remain unknown.…”
Section: Adults With Cerebral Palsymentioning
confidence: 92%